CERITA RAKYAT SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN KARAKTER - Afriani, Vera (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
For the past few years, the number of problems in the field of education has increased and become a focus of attention.Â  Especially those concerning the morality of the students which are degenerating significantly. News such as violence done by students- either to others, or between fellow students, and even the most recent students violence against teachers- has added to the poor records of students bad characters. The students whom we had hoped would one day become the next generations, now even have to deal with legal issues. What a matter of great concern it should be. Therefore, this study aims to give solutions for positive characters to be grown and developed through a learning media such as folktales. Folktales were chosen as a media for they can provide and enrich the knowledge of Indonesian culture to students as well.